Cerebral gliosarcoma with perivascular involvement in a cat. Issue 2 (October 2019) - Álvarez, Patricia; Wessmann, Annette; Pascual, Mireia; Comas, Oriol; Pi, Dolors; Pumarola, Martí
Case summary: A 5-year-old neutered male domestic shorthair cat presented with an 18-month history of facial tics, and progressive general ataxia, weakness, lethargy and anorexia of 2 weeks' duration. MRI of the brain showed a well-defined heterogeneous hyperintense mass on T1-weighted and T2-weighted images, with central hypointensity in the rostral commissure and septum pellucidum, and perilesional hyperintensity in fluid-attenuated inversion recovery, suggestive of perilesional oedema. Gross examination in a transverse section of the brain at the level of the septum pellucidum revealed a 0.2 cm brown soft mass. Histopathological examination identified a biphasic neoplastic proliferation of mesenchymal and neuroepithelial cell populations. Fusiform cells were predominately distributed in bundles showing a high degree of anisocytosis and marked immune-positive reaction to vimentin immunochemistry, confirming a sarcomatous origin. Additionally, high numbers of astrocytic cells were identified by an intense immunopositive reaction to glial fibrillary acidic protein and negative reaction to oligodendrocyte transcription factor 2 immunochemistry. Vascular invasion of the neoplasia into the wall of a medium branch of the rostral cerebral artery was present (secondary Scherer structures). Based on these characteristics, the tumour was defined as a gliosarcoma. Gliosarcoma is a recognised astrocytoma grade IV anaplastic glial cell tumour with sarcomatous differentiation. Relevance and novel information: To our knowledge, this is the first report describing a cerebral gliosarcoma in a cat including clinical, MRI, macroscopic and histopathological features and immunolabelling characteristics.